PHLPP1 deficiency protects against age‐related intervertebral disc degeneration - Changli Zhang; Katherine M. Joseph; Nazir M. Khan; Martha Elena Diaz‐Hernandez; Hicham Drissi; Svenja Illien‐Junger (JOR Spine, 2022)
Abstract Background Intervertebral disc (IVD) degeneration is strongly associated with low back pain and is highly prevalent in the elderly population. Hallmarks of IVD degeneration include cell loss and extracellular matrix degradation. The PH domain leucine‐rich‐repeats protein phosphatase (PHLPP1) is highly expressed in diseased cartilaginous tissues where it is linked to extracellular matrix degradation. This study explored the ability of PHLPP1 deficiency to protect against age‐related spontaneous IVD degeneration. Methods Lumbar IVDs of global Phlpp1 knockout (KO) and wildtype (WT) mice were collected at 5 months (young) and 20 months (aged). Picrosirius red–alcian blue staining (PR‐AB) was performed to examine IVD structure and histological score. The expression of aggrecan, ADAMTS5, KRT19, FOXO1 and FOXO3 was analyzed through immunohistochemistry. Cell apoptosis was assessed by TUNEL assay. Human nucleus pulposus (NP) samples were obtained from patients diagnosed with IVD degeneration. PHLPP1 knockdown in human degenerated NP cells was conducted using small interfering RNA (siRNA) transfection. The expression of PHLPP1 regulated downstream targets was analyzed via immunoblot and real time quantitative PCR. Results Histological analysis showed that Phlpp1 KO decreased the prevalence and severity of age‐related IVD degeneration. The deficiency of PHLPP1 promoted the increased expression of NP phenotypic marker KRT19, aggrecan and FOXO1, and decreased levels of ADMATS5 and cell apoptosis in the NP of aged mice. In degenerated human NP cells, PHLPP1 knockdown induced FOXO1 protein levels while FOXO1 inhibition offset the beneficial effects of PHLPP1 knockdown on KRT19 gene and protein expression. Conclusions Our findings indicate that Phlpp1 deficiency protected against NP phenotypic changes, extracellular matrix degradation, and cell apoptosis in the process of IVD degeneration, probably through FOXO1 activation, making PHLPP1 a promising therapeutic target for treating IVD degeneration.